2015
DOI: 10.1371/journal.pone.0118431
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antimicrobial Activity of Camellia sinensis and Juglans regia against Multidrug-Resistant Bacteria

Abstract: Synergistic combinations of antimicrobial agents with different mechanisms of action have been introduced as more successful strategies to combat infections involving multidrug resistant (MDR) bacteria. In this study, we investigated synergistic antimicrobial activity of Camellia sinensis and Juglans regia which are commonly used plants with different antimicrobial agents. Antimicrobial susceptibility of 350 Gram-positive and Gram-negative strains belonging to 10 different bacterial species, was tested against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 38 publications
2
76
0
Order By: Relevance
“…In a recent study investigating synergistic antimicrobial activity of plant extracts, no significant antimicrobial activity was observed for multidrug resistant A. baumannii [36] . Several in vitro studies reported synergistic effects between diverse drugs for the treatment of Acinetobacter [26,[29][30][31][32]37] .…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study investigating synergistic antimicrobial activity of plant extracts, no significant antimicrobial activity was observed for multidrug resistant A. baumannii [36] . Several in vitro studies reported synergistic effects between diverse drugs for the treatment of Acinetobacter [26,[29][30][31][32]37] .…”
Section: Discussionmentioning
confidence: 96%
“…It is suggested that the antimicrobial action of J. regia against Gram-negative microorganisms must be strain dependent, showing greater effect on Gram-positive microorganisms. Thus, more research on Gram-positive microorganisms with different J. regia extracts could bring better results [2426]. …”
Section: Discussionmentioning
confidence: 99%
“…Biosynthesis of nonstructural polyphenols, which could play a role in pathogen resistance, also was studied in J. regia (Colaric et al 2005;Solar et al 2006;Farooqui et al 2015). The shikimic acid and aromatic amino acid biosynthesis pathways generate precursors of numerous secondary metabolites, such as phenolic compounds.…”
Section: Metabolomics Workmentioning
confidence: 99%